The Effect Of Radio Frequency Spectrum Licensing Service Quality On User Satisfaction In East Java: IPA Analysis And Top Two Box - Dewi Rosiyana Umami (Publikasi Indonesia, 2023)
Hall Monitor SFR Class I Surabaya is a Technical Implementation Unit in charge of supervising and controlling the use of SFR. To determine customer satisfaction with SFR licensing services, research was conducted where the measurement of the satisfaction index was based on 9 indicators, namely Requirements, Service Procedures, Time to Complete, Ease of Payment of Tariffs, Products, Competence of Implementers, Behavior of Implementers, Handling Complaints, Infrastructure. The analysis used to measure satisfaction is the Top Two Boxes Analysis and Importance Performance Analysis methods. Based on the results of the analysis, it was concluded that the Service Satisfaction Index value was 90.84 with service quality A (very good). The results of the IPA 2 indicators must be considered and improved by Balmon Surabaya related to factors that affect customer satisfaction with SFR licensing services. These factors are Complaint Handling and Infrastructure.